2004
DOI: 10.1111/j.1440-1665.2004.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of seclusion in a psychiatric acute inpatient unit

Abstract: Background Seclusion is an intensive intervention employed in inpatient mental health units to guarantee safety when de-escalation methods have been exhausted. High rate of seclusion are associated with higher employee injury rate, lower staff engagement and increased patient length of stay. Objectives Our aim is to reduce seclusion rates in all admitted patients in inpatient psychiatry from a baseline of 136 to less than 110 per 1000 patient days by December 2016 and sustain for 12 months. Methods A multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 7 publications
(8 reference statements)
9
70
1
Order By: Relevance
“…This renders comparisons impossible. The data from other studies is related only to single units [17] (UK), [18] (Australia), [19] (USA) and can therefore not be compared with our data, either. Except for one study from Finland [6] there seems to be no comparable data.…”
Section: Discussionmentioning
confidence: 98%
“…This renders comparisons impossible. The data from other studies is related only to single units [17] (UK), [18] (Australia), [19] (USA) and can therefore not be compared with our data, either. Except for one study from Finland [6] there seems to be no comparable data.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Bowers et al (2010) reported that seclusion was significantly associated with more male nurses on duty (IRR = 1.30, p <.05). Furthermore, lower patient/staff ratios were significantly associated with seclusion (Morrison & Lehane, 1995;Tunde-Ayinmode & Little, 2004), but not all authors found this association (e.g. Vollema et al (2012) and Husum, Bjorngaard, Finset, and Ruud (2010)).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies on this matter collected data retrospectively (Janssen et al, 2007;Nijman et al, 1994;Vollema et al, 2012), used a cross-sectional design (Bowers et al, 2010) or primarily addressed patient-staff ratios (Morrison & Lehane, 1995;Tunde-Ayinmode & Little, 2004). One of the strengths of our study is that we used a rigorous, census-based, prospective design to collect data.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One specific issue to consider in PICUs is the dimension of violence, which is the most common reason for admission (Dolan & Lawson, 2001;Pereira et al, 2005), and patients should be considered as high risk (Wynaden et al, 2001). Earlier research focuses in large part on managing violent behavior using pharmacological intervention (Pilowsky et al, 1992), seclusion rooms (El-Badri & Mellsop, 2002;Tunde-Ayinmode & Little, 2004), and mechanical restraints (Kaltiala-Heino et al, 2003). Nelstrop et al (2006) emphasize that there is a lack of evidence to support the use of seclusion and restraints as safe and effective measures, and that these should be used only as a last resort.…”
Section: Introductionmentioning
confidence: 99%